Analysis of I-V Characteristics of Silicon PIN Diodes - Nasir, Nur Niwina; Mat Jubadi, Warsuzarina (Evolution in Electrical and Electronic Engineering, 2024)
PIN diodes are a special kind of semiconductor that are used widely in microwave and radio frequency (RF) circuits because they function as current-controlled resistors at these frequencies. This research focuses on simulating the effects of varying intrinsic region widths on the I-V characteristics. The investigation spans a range of intrinsic region widths from 2.5 µm to 175 µm using Sentaurus TCAD to design a silicon PIN diode structure. Results show a consistent decrease in forward current as the intrinsic region width increases. The study provides essential insights for optimizing PIN diode performance in high-frequency applications, validated through comparison with theoretical calculations. The results show that the forward current through the PIN diode decreases as the intrinsic region width increases when compared to theoretical calculations. At a thickness of 2.5 µm, the calculated current value is 2.24 µA, a slightly higher than the simulated value of 2.12 µA. However, as the thickness increases, the difference becomes more noticeable. At 6 µm, the calculated current value rose to 5.38 µA, while the simulated value drops to 1.19 µA. The I-V curves illustrate this relationship, indicating that widening the intrinsic region leads to a reduction in current flow. This finding provides valuable insights for optimizing PIN diode performance in high-frequency applications.